Assessing the impacts of climate changes and human activities on cotton distribution in Xinjiang - Wang, Shanshan; Shi, Mingjie; Fan, Yanmin; Jiang, Pingan; Chen, Shuhuang; Li, Yunhao; Huang, Lijie; Zhao, Jiahao (Frontiers in Sustainable Food Systems, 2025)
Both climate change and human activities play critical roles in shaping the spatial distribution of cotton cultivation, particularly in arid and semi-arid environments. However, existing studies have not sufficiently quantified their synergistic effects, and regional-scale applications remain limited. This study selected key variables from 31 environmental factors—including climate, soil, topography, and human footprint—and employed an optimized MaxEnt model to project cotton distribution across three Shared Socioeconomic Pathways (SSP126, SSP245, and SSP585). We developed models based on (i) current climate conditions, (ii) an integrated model incorporating both current climate conditions and human footprint, and (iii) future climate projections for the 2030s, 2050s, and 2070s. The results indicate that human footprint, mean diurnal temperature range (bio2), mean temperature of the coldest quarter (bio11), precipitation of the coldest quarter (bio19), and solar radiation intensity are the primary factors influencing cotton distribution. Under prevailing climate conditions, suitable cotton habitats are mainly located in Aksu, Kashgar, Tacheng, Bayingolin Mongol Autonomous Prefecture, and Changji, where human activities have significantly expanded the cultivation range. Future climate projections indicate a decrease in the extent of suitable cotton habitats, with its distribution center shifting toward lower-altitude areas. This study offers key empirical evidence and conceptual understanding to address climate-induced risks to cotton farming, forming a basis for informed strategies in sustainable cultivation and habitat conservation.